Effects of Different Inclusion Levels of Moringa oleifera Leaf Meal (MLM) on the Fecundity and Gonadosomatic Index (GSI) of the African Catfish Heterobranchus longifilis - Opeh, Patience Bassey; Eyo, Victor Oscar; Udo, Paul Jimmy (Asian Journal of Advances in Agricultural Research, 2018)
This study was conducted to evaluate the effect of varying inclusion levels of Moringa oleifera leaf meal (MLM) on fecundity and gonado-somatic index (GSI-%) of the African catfish Heterobranchus longifilis. Fifteen (15) tarpaulin unit measuring 100 by 80 by 100 cm was used to aid triplication of the five experimental groups. Five isonitrogenous diets (43% cp) including Diet A (control), Diet B (5% MLM), Diet C (10% MLM), Diet D (15% MLM) and Diet E (20% MLM) were used for this study. A total of three hundred (300) healthy fingerlings of H. longifilis with mean bulk body weight 361.60 ± 0.3 g and total length 11.15 ± 0.04 cm were stocked in the 15 units (20 in each unit). Results of the proximate composition showed that M. oleifera leaf meal (MLM) had a rich nutritional profile with crude protein level of 27.80 ± 0.02%, ash (6.45 ± 0.02%), crude fibre (18.50 ± 0.01%), crude fat (2.72 ± 0.02%), moisture (8.36 ± 0.03%) and nitrogen-free extract (36.17 ± 0.02%). Mean fecundity was significantly higher (P<0.05) in fish fed Diet C (10% MLM) with 71195.25 ± 9551 eggs, followed by fish fed Diet D (15% MLM) with 59085.50 ± 8208 egg and least in fish fed Diet A (control) with 43150.75 ± 7964 eggs. Female fish fed Diet C (10% MLM) had the highest GSI value of 9.93 ± 0.87% which was significantly different (P<0.05) from other treatments and the least female GSI 9.93 ± 0.87% was obtained in fish fed Diet A (control). Similarly, male GSI was significantly higher (P<0.05) in fish fed Diet C (10%MLM) with a value of 0.94 ± 0.04% and least (0.79 ± 0.06%) in fish fed Diet A (control). There was no significant difference (P>0.05) in food conversion ratio (FCR), and food conversion efficiency of fish fed all the experimental diets. In conclusion, incorporation of M. oleifera leaf meal (MLM) in the diet of H. longifilis at 15% level will result in a higher fecundity and improved gonadal development.
Keywords: Heterobranchus longifilis; Moringa oleifera leaf meal; fecundity; gonado-somatic index; varying inclusion levels